Sociotechnical Network Analysis for Power Grid Resilience in South Korea. (23rd October 2017) - Eisenberg, Daniel A.; Park, Jeryang; Seager, Thomas P.
Abstract : International efforts to improve power grid resilience mostly focus on technological solutions to reduce the probability of losses by designing hardened, automated, redundant, and smart systems. However, how well a system recovers from failures depends on policies and protocols for human and organizational coordination that must be considered alongside technological analyses. In this work, we develop a sociotechnical network analysis that considers technological and human systems together to support improved blackout response. We construct corresponding infrastructure and social network models for the Korean power grid and analyze them with betweenness to identify critical infrastructures and emergency management organizations. Power grid network analysis reveals important power companies and emergency management headquarters for responding to infrastructure losses, where social network analysis reveals how information-sharing and decision-making authority shifts among these organizations. We find that separate analyses provide relevant yet incomplete recommendations for improving blackout management protocols. In contrast, combined results recommend explicit ways to improve response by connecting key owner, operator, and emergency management organizations with the Ministry of Trade, Industry, and Energy. Findings demonstrate that both technological and social analyses provide important information for power grid resilience, and their combination is necessary to avoid unintended consequences for future blackout events.